Le transmédia : un dépassement du médium ? - Karleen Groupierre (Appareil)
In a world marked by the emocratization of new technologies, immersive works spread over multiple supports appear: transmedia fictions. Those transmedia art works seems to lead to a transformation of the uses of the medium in artistic creation. Indeed, each author decides usually the way to transform an idea into an art piece, according to his own skills, experiences, area of expertise and his favorite medium. When a painter creates and before he even takes a brush, he mentally foresees the pigments he wants to use, the canvas grain or colors smoothness. In momentum of anticipation, he will transform the material in a medium. But, what could foresee a versatile artist who is aware of music, digital interfaces, painting, games and videos? What material will be chosen by an author who has no predilection for a specific way of realization? Could he not see a hybrid art work realized using simultaneously various creative ways, in other words a transmedia? So, some authors could be able to create without the limit of a predilection for a specific medium; they would be transmedia authors, having an impressive range of medium and all gathered to form a unique artwork?